Elite biathlon: static/dynamic postural control training in shooting practices - Muraleeva, E. V.; Chumakov, V. N.; Karintsev, I. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to offer theoretical grounds for an static/ dynamic balance training model for biathlon elite customizable to the individual progress needs.